2020
DOI: 10.18632/aging.103417
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgM against SARS-CoV-2 correlates with in-hospital mortality in severe/critical patients with COVID-19 in Wuhan, China

Abstract: Severe/critical patients with coronavirus disease 2019 (COVID-19) have become the central issue in the current global pandemic due to their high mortality rate. However, the relationship between antibody response and clinical outcomes has not been well described in this group. We conducted a single-center, retrospective, cohort study to investigate the relationship between serum immunoglobulin G (IgG) and IgM and clinical outcomes in severe/critical patients with COVID-19. Seventy-nine severe/critical patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
1
23
1
2
Order By: Relevance
“…A single-center retrospective study showed that (Liu X. et al, 2020 ) COVID-19 patients with severe/critical had a higher risk of clinical adverse events when the IgM titer was higher than 50 AU/ml, and a lower IgM titer in severe/critical patients may indicate a better prognosis. Hou et al found that (Hou et al, 2020 ) IgM levels in COVID-19 patients with severe and critical disease were higher than those in patients with mild disease, while IgG levels in patients with critical disease were lower than those in patients with mild and severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center retrospective study showed that (Liu X. et al, 2020 ) COVID-19 patients with severe/critical had a higher risk of clinical adverse events when the IgM titer was higher than 50 AU/ml, and a lower IgM titer in severe/critical patients may indicate a better prognosis. Hou et al found that (Hou et al, 2020 ) IgM levels in COVID-19 patients with severe and critical disease were higher than those in patients with mild disease, while IgG levels in patients with critical disease were lower than those in patients with mild and severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…As of December 21, around 75 million infections have been documented around the globe with an overall mortality rate of 2.23% [ 1 ]. Although most patients with SARS-CoV-2 infections have been reported to develop mild to moderate symptoms, patients with severe respiratory insufficiency requiring admission to the intensive care unit (ICU) are at a high risk of major morbidity and subsequently have high mortality rates [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. Several cohort studies have reported the characteristics of and outcomes from COVID-19 pneumonia in these critically ill patients [ 2 , 4 , 5 , 11 , 12 , 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Phipps et al reported that antibody responses were ineffectual at predicting disease progression [ 8 ]. In contrast, Liu et al found that serum IgM titer changes as COVID-19 progresses, and high levels of IgM are associated with acute respiratory distress syndrome (ARDS) in severe/critical patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%